Kompaktifikasi dari Teori Superstring dan Teori-M - Freddy P. Zen; Bobby E. Gunara; Bintoro A. Subagyo; Zulfi Zulfi; Asep Y. Wardaya (Institut Teknologi Bandung, 2003)
Compactification of the five consistent supertring theories, i.e. type IIA, type IIB, type I, heterotic SO (32) , and heterotic E8 ⊗ E8 on six dimensional compact manifold are considered. Explicitly we discuss compactification of heterotic string on toroidal, orbifold and Calabi-Yau manifold. It yields a mass spectrum on low energy from those compactification. We also discussed SO(2N) and SU(N) enhanced gauge symmetry as a byproduct of compactification on M theory (11 dimensions) which is dual with type IIA superstring theory (10-dimensions). In this case, we can get enhanced gauge symmetry at singular point in the moduli space on a K3 surface.